Pengaruh Good Corporate Governance terhadap kinerja keuangan perusahaan perbankan yang terdaftar di Bursa Efek Indonesia Pada Periode 2017-2021 - Tjua, Stefanie Monika; Masdjojo, Gregorius N. (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this study is to determine the effect of applying the principles of Good Corporate Governance on the financial performance of banking companies listed on the Indonesian stock exchange for the 2017-2021 period. This study uses quantitative methods with secondary data, namely in the form of company annual reports obtained from www.idx.co.id and the company's official website. The independent variable in this study is Good Corporate Governance which is focused on four aspects, namely the Independent Board of Commissioners, the Audit Committee, Institutional Ownership, and Company Size. The dependent variable used is the financial performance of banking companies as proxied by Return On Assets (ROA). The sample was selected using the purposive sampling method with a total of 100 samples and processed using panel data regression. The results showed that the Independent Board of Commissioners and Institutional Ownership had no effect on the Financial Performance of Banking Companies, while the Audit Committee and Company Size had a significant effect on the Financial Performance of Banking Companies. While the Independent Board of Commissioners, Audit Committee, Institutional Ownership, and Company Size together have a significant effect on the Financial Performance of Banking Companies.